A device for measuring sternal bone connectivity using vibration analysis techniques. (January 2020) - Joutsen, Atte; Hautalahti, Juha; Jaatinen, Esa; Goebeler, Sirkka; Paldanius, Antti; Viik, Jari; Laurikka, Jari; Hyttinen, Jari
Objectives: Stability of bone splitting sternotomy is essential for normal healing after open cardiac surgery. Mechanical vibration transmittance may offer a means for early detection of separation of bone (diastasis) in the sternotomy and prevent further complications. This article describes the technical implementation and validation of vibration analysis–based prototype device built for measuring sternal bone connectivity after sternotomy. Methods: An in-house built measurement system, sternal vibration device, consisting of actuator, sensor, and main controller and signal acquisition unit was designed and manufactured. The system was validated, and three different test settings were studied in mockups (polylactide rods in ballistic gel) and in two human sternums: intact, stable wire fixation, and unstable wire fixation with a gap mimicking bone diastasis. The transmittance of vibration stimulus across the median sternotomy was measured. Results: The validation showed that the force produced by the actuator was stable, and the sensor could be calibrated to precisely measure the acceleration values. The vibration transmittance response to material cut and sternotomy was evident and detectable in the 20 Hz to 2 kHz band. The transmittance decreased when the connectivity between the sternal halves became unstable. The trend was visible in all the settings. Conclusion: Technical solutions and description of validation process were given. The device was calibrated, and the vibration transmittance analysis differentiated intact and cut polylactide rod. In the sternum, intact bone, wire fixation with exact apposition, and with a gap were identified separately. Although further studies are needed to assess the accuracy of the method to detect different levels of diastases, the method appears to be feasible.